A NEW SPECIES OF BARLERIA (ACANTHACEAE) FROM OMAN - KNEES, S. G.; LASER, S.; MILLER, A. G.; PATZELT, A. (Edinburgh Journal of Botany, 2007)
A new species of Barleria (Acanthaceae), Barleria samhanensis Knees, A.G.Mill. & A.Patzelt, is described from southern Oman and a provisional assessment of its conservation status is provided. Further support is given for the recognition of the summit of Jabal Samhan as a distinct floristic unit.